Corrosion and conservation of cultural heritage metallic artefacts - Dillmann, P. (Philippe) (European Federation of Corrosion (EFC) Series., 2013)
The conservation of metallic archaeological and historic artefacts is a major challenge whether they are ancient bronzes or relics of our more recent industrial past. Based on the work of Working Party 21 Corrosion of Archaeological and Historical Artefacts within the European Federation of Corrosion (EFC), this important book summarises key recent research on analytical techniques, understanding corrosion processes and preventing the corrosion of cultural heritage metallic artefacts. After an introductory part on some of the key issues in this area, part two reviews the range of analytical techniques for measuring and analysing corrosion processes, including time resolved spectroelectrochemistry, voltammetry and laser induced breakdown spectroscopy. Part three reviews different types of corrosion processes for a range of artefacts, whilst part four discusses on-site monitoring techniques. The final part of the book summaries a range of conservation techniques and strategies to conserve cultural heritage metallic artefacts. Corrosion and conservation of cultural heritage metallic artefacts is an important reference for all those involved in archaeology and conservation, including governments, museums as well as those undertaking research in archaeology and corrosion science. Summarises key research on analytical techniques for measuring and analysing corrosion processesProvides detailed understanding of corrosion processes and corrosion preventionDiscusses on-site monitoring techniques.